PENGARUH MODEL STUDENT FACILITATOR AND EXPLAINING BERBANTUAN MEDIA VISUAL NON PROYEKSI TERHADAP KOMPETENSI PENGETAHUAN IPA - Ana Saisabila (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the influence and the effect size of student facilitator and explaining learning model, assisted by non-projection visual media toward the science knowledge competences of fourth grade students at SD Gugus Letda Made Putra North Denpasar 2017/2018 academic year. The type of this research is quasi experimental with non-equivalent control group design. The population of this research was 11 group classes of fourth grade students at SD Gugus Letda Made Putra North Denpasar which amount to 393 students. The sampling technique used in this research is the group sample technique. The sample of this study was consist of 2 groups; experimental group and control group. Each group was given a pre-test and then measured by using the t-test to determine its equality. The data of science knowledge competences were obtained through a test of multiple choice questions. After obtaining the post-test data of science knowledge competences, the data were analyzed by using t-test with polled variance formula. The average post-test score of the students in the experimental group is 75,37 and the average student in the control group is 68,25. Based on the 5% of significance level and the dk = 71, the result obtains the tcount = 2,147 > ttable = 1,994. Thus, there is a significant difference of science knowledge competences between the experimental group and the control group. It can be concluded that student facilitator and explaining learning model assisted by non-projection visual media has a significant influence toward science knowledge competences of fourth grade students at SD Gugus Letda Made Putra Nort Denpasar 2017/2018 academic year. The calculation of the effect size model to science knowledge competences is done by calculating the Cohen's d Coefficient, which obtains value d = 0,51 with medium effect category.